Natural Polyphenols in Human Health (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Polyphenols are natural phytochemicals recognized as one of the largest and most widespread classes of plant constituents occurring throughout the plant kingdom. Over the years, polyphenols have attracted the attention of the scientific community due to their potential health-promoting effects. Owing to their several interesting properties, polyphenols have aroused considerable interest, shedding light on their chemistry, reactivity, biological properties and their beneficial effects on both plants and humans. As a result of these investigations, a huge number of research works have been reported on polyphenols. However, despite the voluminous literature studying polyphenols and their impact on human health, there are still many issues waiting to be explored in order to explain and elucidate the positive effects of polyphenols on human health. This Special Issue was intended to gather up-to-date knowledge related to the cutting-edge research in the broad scientific area of polyphenols, providing an opportunity to show the latest advances in the exploration of polyphenols and their health beneficial effects. The special issue was a great success with more than 50 published manuscripts covering various aspects related to polyphenols and their role in human health. We are confident that this Special Issue will be of great interest to the scientific community, and will contribute to the improvement of knowledge regarding the area of polyphenols, leading to a better understanding of their role in human health.